2020
DOI: 10.1007/s42729-020-00377-w
|View full text |Cite
|
Sign up to set email alerts
|

Organic Fertilization Improves the Availability and Adsorptive Capacity of Phosphorus in Saline-Alkaline Soils

Abstract: Organic fertilizer could improve soil phosphorus (P) availability and retention capacity, and the intensive management of P nutrition in saline alkaline paddy soil is of great significance to the sustainable development of rice planting. The P fractions and adsorption-desorption characteristic in saline-alkaline soils were evaluated in a 5-year field experiment. Four treatments were designed: (1) NK (255 kg N ha −1 year −1 and 229 kg K ha −1 year −1), (2) NPK (128 kg P 2 O 5 ha −1 year −1 plus NK), (3) NPKC1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 47 publications
(72 reference statements)
0
6
1
Order By: Relevance
“…This can be attributed to the supply of nutrients afforded by organic fertilizers, which increases the soil P content (Table 3), particularly at lower salinity levels, and to the fact that the nutrient is also extracted from the soil solution by the plant during its cycle, what can also reduce its levels in the soil. Contrary to the present study, Mengmeng et al (2021) found an increase in the levels of available phosphorus in soil affected by salts, when using organic fertilizer.…”
Section: Resultscontrasting
confidence: 99%
“…This can be attributed to the supply of nutrients afforded by organic fertilizers, which increases the soil P content (Table 3), particularly at lower salinity levels, and to the fact that the nutrient is also extracted from the soil solution by the plant during its cycle, what can also reduce its levels in the soil. Contrary to the present study, Mengmeng et al (2021) found an increase in the levels of available phosphorus in soil affected by salts, when using organic fertilizer.…”
Section: Resultscontrasting
confidence: 99%
“…As leaf residues of plants, pine needles have more soluble nutrients than the other materials; their nitrogen and phosphorus elements exhibit a trend of first enrichment, then release, and gradually increasing, allowing them to permanently assist organic acid fertilization and directly increase soil nutrient content ( Gao et al., 2019 ; Manral et al., 2020 ). The colloidal properties of cow manure can enhance the bonding of organic and inorganic complexes, promote the formation of soil aggregates and the accumulation of organic matter, and effectively enhance the availability and retention of nutrients ( Chen et al., 2021a ). However, its own nutrient content is relatively low, and the overall effect of combining the activation function of an organic acid with cow manure is slightly lower than that compared with pine needles.…”
Section: Discussionmentioning
confidence: 99%
“…On preprocessed satellite imagery, applied the basic binary operation of digital image processing to measure the multitemporal change of reduction in the pollutants of air at the level of surface [22].…”
Section: Change Of Air Pollutantsmentioning
confidence: 99%